1995
DOI: 10.1017/s0008938900012292
|View full text |Cite
|
Sign up to set email alerts
|

From Emigration to Immigration: The German Experience in the Nineteenth and Twentieth Centuries

Abstract: United Germany has become more ethnically divers and, to a certain extent, more “multicultural” with a growing minority of immigrants and temporary migrants living within its borders. There are labor migrants from Southern and Eastern Europe with restricted work permits, immigrants coming out of the former “guest worker” population, and ethnic Germants from Eastern Europe as well as various groups of asylum seekers and other refugees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…52 Throughout the nineteenth and early twentieth centuries, the United States was the primary destination for Germans, although a sizeable element settled in the British Isles. 53 Panayi argues that some transmigrants en route to North America ended up in the UK unintentionally. 54 A significant portion of the German-born population of the British Isles had fled from military service, including many of the Speidel family.…”
Section: The Journal Of Genealogy and Family Historymentioning
confidence: 99%
“…52 Throughout the nineteenth and early twentieth centuries, the United States was the primary destination for Germans, although a sizeable element settled in the British Isles. 53 Panayi argues that some transmigrants en route to North America ended up in the UK unintentionally. 54 A significant portion of the German-born population of the British Isles had fled from military service, including many of the Speidel family.…”
Section: The Journal Of Genealogy and Family Historymentioning
confidence: 99%
“…To explore this we can begin with Germany, a country that has, until relatively recently, displayed a long tradition of recruiting "guest workers" from neighboring countries. Between the 1890s and the First World War, during a period of rapid industrial growth, it saw large numbers of seasonal workers from Poland and the Austro-Hungarian and Russian Empires to address labor shortages (Bade, 1995). During the Weimar Republic, fewer numbers were recruited, as a result of the Great Depression and rules that allowed foreign labor only if it could be shown that no German workers were available.…”
Section: Germany and Denmark: The Backlash In Nonmulticultural Statesmentioning
confidence: 99%
“…Računalo se da će u vrijeme konjunkture migranti osigurati potrebnu radnu snagu (a bez nekih važnijih društvenih i sindikalnih prava), a s nastupom krize vraćat će se kući. Širilo se mišljenje da taj model odgovara ne samo domaćinima već i samim migrantima te zemljama podrijetla (Bade, 1997). No s vremenom je ojačalo pretvaranje privremenih radnika migranata u trajne migrante; radnik u inozemstvu postaje iseljenik.…”
Section: Razdoblje 1948 -1991unclassified